2006
DOI: 10.1007/s11745-006-5075-9
|View full text |Cite
|
Sign up to set email alerts
|

The real radical generator other than main‐product hydroperoxide in lipid autoxidation

Abstract: The theory of initiation in lipid autoxidation, which deals with the supply of radicals to the chain reaction, has not been substantively advanced for several decades. Most researchers have long assumed a mechanism of initiation in which main-product hydroperoxide is centrally responsible for autocatalytic radical generation. However, this paper, in which we investigate autoxidizing methyl linoleate, presents decisive evidence against such an assumption: Autoxidation-accelerating activity under mild conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 14 publications
2
31
1
Order By: Relevance
“…Although H(P)NE was not mentioned, other interesting aldehydes, including hexanal, 2-octenal, and 2,4-decadienal, important in food technologies, received mechanistic attention. The work culminated in identification of the active components as peroxide-linked dimers containing two hydroperoxy groups (37). Their overall conclusion is that radical generation and aldehyde production are two facets of the same process, sparked by the inherent instability of the dimeric peroxyhydroperoxides.…”
Section: Involvement In the Initiation Of Lipidmentioning
confidence: 99%
“…Although H(P)NE was not mentioned, other interesting aldehydes, including hexanal, 2-octenal, and 2,4-decadienal, important in food technologies, received mechanistic attention. The work culminated in identification of the active components as peroxide-linked dimers containing two hydroperoxy groups (37). Their overall conclusion is that radical generation and aldehyde production are two facets of the same process, sparked by the inherent instability of the dimeric peroxyhydroperoxides.…”
Section: Involvement In the Initiation Of Lipidmentioning
confidence: 99%
“…Recently, however, Morita & Tokita (2006 reported that in methyl linoleate autoxidation the non-hydroperoxide peroxides that are responsible for the autocatalytic activity consist of two peroxide-linked linoleate moieties with two hydroperoxyl groups. Such dimer fatty acids would be prone to breakage of the cross-molecular peroxide bond and would produce, as depicted in Fig.…”
Section: Autoxidationmentioning
confidence: 99%
“…Hence, the ability of a high concentration of -tocopherol to promote hydroperoxide formation was exploited in studies I to IV. It is difficult, however, to estimate the importance of the reactions that account for the pro-oxidant properties of -tocopherol, because it is plausible, based on the recent studies on the initiation process of methyl linoleate (Morita & Tokita 2006, that unstable oligomeric peroxides are the main source of autocatalytic radicals also in the autoxidation of CLA methyl esters.…”
Section: Role Of -Tocopherol (I To Iv)mentioning
confidence: 99%
“…In our previous paper [6], the lack of autocatalytic activity was also clearly showed by using a highly rigorous and sensitive detecting method when the purified main-product hydroperoxide of methyl linoleate was examined under the usual storage conditions and at body temperature; in addition, a type of substance revealing potent autocatalytic activity was found in autoxidizing methyl linoleate.…”
Section: Introductionmentioning
confidence: 92%
“…Scheme 1 We assumed [6] that the mechanism of their homolytic decomposition and radical supply is an energetically favorable concerted one as depicted also in Scheme 1. The mechanism predicted the formation of hydroxy radicals and hexanal as direct products of the homolysis, and the formation of 2,4-decadienal via the b-scission route from linoleate-skeleton alkoxy radicals.…”
Section: Introductionmentioning
confidence: 99%